Water quality comparison for various drainage systems for 2000 equivalent population - Hluštík, Petr; Raclavský, Jaroslav (IOP Publishing, 2020)
The article deals with the comparison of wastewater quality in gravity and alternative drainage systems. The gravity drainage systems include combined and sanitary sewerage systems, the alternative systems encompass pressure and vacuum sewerage systems. The difference in the quality of wastewater conveyed to a wastewater treatment plant is influenced by the relevant sewerage system, its technical condition and regular maintenance. The objective of the article is to highlight the differences in wastewater quality with respect to BOD, COD, SS, NH4, Nt and Pct indicators based on the chemical analyzes conducted over several years of operation. The comparison is made for selected municipalities in the Czech Republic in 2005-2019 for various sewerage systems.

The article deals with the comparison of wastewater quality in gravity and alternative drainage systems. The gravity drainage systems include combined and sanitary sewerage systems, the alternative systems encompass pressure and vacuum sewerage systems. The difference in the quality of wastewater conveyed to a wastewater treatment plant is influenced by the relevant sewerage system, its technical condition and regular maintenance. The objective of the article is to highlight the differences in wastewater quality with respect to BOD, COD, SS, NH4, Nt and Pct indicators based on the chemical analyzes conducted over several years of operation. The comparison is made for selected municipalities in the Czech Republic in 2005-2019 for various sewerage systems.
Water quality comparison for various drainage systems for 2000 equivalent population
Keywords: waste water quality; gravity; pressure and vacuum sewerage; waste water transport; waste water quality; gravity; pressure and vacuum sewerage; waste water transport